Cerogobius petrophilus (Perciformes: Gobiidae), a new gobiid genus and species from the Red Sea - Kovačić, Marcelo; Bogorodsky, Sergey V.; Troyer, Emily M.; Tornabene, Luke (Zootaxa, 2019)
A new genus and species of cryptobenthic goby, Cerogobius petrophilus is described from the Red Sea based on nine specimens not exceeding 2.5 cm in total length, collected from a stone-rubble habitat at Thuwal, Saudi Arabia, at depths of 8–15 m. It was also observed underwater at the southern tip of Ras Mohammed and Marsa Alam in Egypt. Cerogobius petrophilus sp. nov. is unique among other gobies in its habitat, and in this regard it superficially resembles some species of blennies, occupying tight holes in stones covered with short algae. Molecular phylogenetic data suggest a close relationship between Cerogobius petrophilus sp. nov. and Hetereleotris, but the former differs from the latter morphologically in head shape with specific proportions of orbit and snout, forward-set position of eyes, a moderately large mouth, a long horn-like tentacle at the nostrils in the middle of snout, caudal peduncle deep and short, and in details of cephalic sensory system. A full description of the new genus and species is provided and is accompanied with osteological data that potentially can be informative in further comparisons with Hetereleotris.